Experience with the surgical treatment of atrioventricular septal defect with left ventricular outflow tract obstruction†. (28th February 2014) - Tlaskal, Tomas; Gebauer, Roman; Gilik, Jiri; Tomek, Viktor
Abstract: OBJECTIVES: We sought to determine the prevalence, morphology, surgical methods and results of surgery for left ventricular outflow tract obstruction (LVOTO) associated with atrioventricular septal defect (AVSD). METHODS: Correction of AVSD was performed in 615 patients. Twenty-three (3.7%) patients with LVOTO were identified. Sixteen (70%) of them had partial and 7 (30%) had complete AVSD. Surgery for AVSD was performed at a median of 0.6 years (mean 2.1 ± 3.0 years), and surgery for LVOTO at a median of 3.4 years (mean 4.7 ± 3.5 years). The point and period prevalence of LVOTO in AVSD were determined. Detailed morphological study, individualized repair of AVSD with LVOTO and long-term follow-up were performed. Early and long-term results were analysed. RESULTS: The point prevalence of LVOTO at the time of AVSD repair was 1.3%. The period prevalence of LVOTO was 3.7% in course of 8.3 ± 6.0 (0–18.4) years and 191.4 patient-years following AVSD repair. Causes of LVOTO were fibromuscular membrane ( n = 17), septal hypertrophy ( n = 17), abnormal atrioventricular (AV) valve ( n = 9), muscular bands ( n = 3), fibrous strands ( n = 4) and stenotic aortic valve ( n = 2). Usually, a combination of several obstructive lesions was present. LVOTO was present at the time of AVSD repair in 8 patients (35%) and developed after repair in 15 (65%) patients. Membrane excision ( n = 17), myectomy ( n = 17), excision of abnormal AV valvar tissue ( n = 8), excision of muscular bands and fibrous strands ( n = 6), AV valve replacement ( n = 2) and aortic valvotomy ( n = 2) were required. There was 1 (4%) early and 1 (4%) late death. Six (29%) survivors required reoperation for recurrence of LVOTO at an average interval of 6.3 ± 3.2 years after surgery. The actuarial survival at 1 and 10 years was 96 and 88%, respectively. The actuarial freedom from reoperation for LVOTO was 80, 40 and 20% at 6, 10 and 15 years after surgery, respectively. Eighteen (78%) patients remain in good condition at mean 6.0 ± 5.5 years after surgery. CONCLUSIONS: The point prevalence of LVOTO at the time of AVSD repair was 1.3%, and period prevalence 3.7%. Fibromuscular membrane, septal hypertrophy and valvar attachments represent the most common causes of LVOTO. Usually, more structures are involved. The repair must be individualized. The presence of LVOTO increases the need for reoperation.